1977
DOI: 10.1111/j.1432-1033.1977.tb11522.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between beta-Lactam Antibiotics and Isolated Membranes of Streptococcus faecalis ATCC 9790

Abstract: The DD-carboxypeptidase -exchange membrane-bound enzyme in Streptococcus faecalis ATCC 9790 reacts with p-lactam antibiotics to form complexes with rather long half-lives. Depending upon the antibiotic, the second-order rate constants for complex formation range from 0.75 -560 M-' s-l (at 37 "C and in water) and the first-order rate constants for complex breakdown range from 1.3 to 26 x lo-' s-' (at 37 "C and in 5 mM phosphate buffer pH 7.5). There are about 30 pmol of DD-carboxypeptidase -exchange enzyme per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Saturation curves indicated that maximal binding of [14C]benzylpenicillin to growing cells (using the conditions described in Materials and Methods) and to isolated membranes (as described in [2] …”
Section: Binding Of ('4c]benzyllenicillin To Intuct Cells and Isolatmentioning
confidence: 99%
See 2 more Smart Citations
“…Saturation curves indicated that maximal binding of [14C]benzylpenicillin to growing cells (using the conditions described in Materials and Methods) and to isolated membranes (as described in [2] …”
Section: Binding Of ('4c]benzyllenicillin To Intuct Cells and Isolatmentioning
confidence: 99%
“…linkage of the J-lactam ring [1,2]. Spontaneous breakdown (at pH 7.5) of the complexes formed between [14C]benzylpenicillin and the isolated membrane (thus involving all the penicillin-binding proteins present) also causes regeneration of the membrane-bound DD-carboxypeptidase activity [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation